The Oxford handbook of megaproject management - Flyvbjerg, Bent (Oxford : Oxford University Press, 2017)
This handbook is currently in development, with individual articles publishing online in advance of print publication. At this time, we cannot add information about unpublished articles in this handbook, however the table of contents will continue to grow as additional articles pass through the review process and are added to the site. Please note that the online publication date for this handbook is the date that the first article in the title was published online.
Introduction: The Iron Law of Megaproject Management / Bent Flyvbjerg -- Megaproject Escalation of Commitment: An Update and Appraisal / Helga Drummond -- Understanding Drivers of Megaevents in Emerging Economies / Robert A. Baade, Victor A. Matheson -- Megaprojects as Games of Innovation / Roger Miller, Donald Lessard, Vivek Sakhrani -- Megaproject Stakeholder Management / Graham M. Winch -- Innovation and Flexibility in Megaprojects: A New Delivery Model / David M. Gann, Andrew Davies, Mark Dodgson -- Private Finance: What Problems Does It Solve, and How Well? / Carsten Greve, Graeme A. Hodge -- Quality Assurance in Megaproject Management: The Norwegian Way / Knut Samset, Gro Holst Volden -- Wider Impacts of Megaprojects: Curse or Cure? / Roger Vickerman -- The Power of Systems Integration: Lessons from London 2012 / Andrew Davies -- Has Megaproject Management Lost Its Way? Lessons from History / Sylvain Lenfle, Christoph Loch -- Iconic Urban Megaprojects in a Global Context: Revisiting Bilbao / Gerardo del Cerro Santamaria -- Megaprojects as Political Symbols: South Africa's Gautrain / Janis van der Westhuizen -- The Good Megadam: Does It Exist, All Things Considered? / Thayer Scudder -- Cracking the Code of Megaproject Innovation: The Case of Boeing's 787 / Vered Holzmann, Aaron Shenhar, Yao Zhao, Benjamin Melamed -- Private Provision of Public Services: The Case of Australia's Motorways / Demi Chung -- Large Dam Development: From Trojan Horse to Pandora's Box / Rhodante Ahlers, Margreet Zwarteveen, Karen Bakker -- A Collective-Action Perspective on the Planning of Megaprojects / Nuno Gil -- Cycles in Megaproject Development / Matti Siemiatycki -- Institutional Challenges and Solutions for Global Megaprojects / W. Richard Scott, Raymond Levitt -- Big is Fragile: An Attempt at Theorizing Scale / Atif Ansar, Bent Flyvbjerg, Alexander Budzier, Daniel Lunn -- Biggest Infrastructur
Includes bibliographical references.
Description based on online resource; title from home page (viewed on September 1, 2017).
Keywords: Project management